Application of Discovery Learning Learning Model to Improve Learning Outcomes of Fourth Grade Learners - Muhamad Hatta; Heris Hendriana; Wikanengsih Wikanengsih (JLER (Journal of Language Education Research), 2023)
The purpose of this research is to improve learners' learning outcomes through the application of Discovery Learning models. The type of research used is Class Action Research (PTK). The subject of the study was a class IV student of SDN Talagasari 3 Karawang City. Data collection techniques use tests, observation data, and rubric activities of Teachers and Learners. Data analysis techniques are used in the form of quantitative and qualitative descriptive. The learning outcomes of 28 learners in the first cycle study of IPA subject content with KKM 67 showed that as many as 19 learners had reached KKM if it was percentage to 68%. While 11 students have not reached KKM if the percentage becomes 32%. Then the results of the Second Cycle study increased when compared to cycle I which was (93%) or as many as 26 completed learners. Based on these data, it can be concluded that learning outcomes in cycle II have reached the target of 85%. Thus thr application of the Discovery Learning learning model can improve the learning outcomes of class IV learners of SDN Talagasari 3 Karawang City.